Neutrosophic general finite automata - J., Kavikumar; D., Nagarajan; Said, Broumi; F., Smarandache; M., Lathamaheswari; Ebas, Nur Ain (2019)
The constructions of finite switchboard state automata is known to be an extension of finite automata in the view of commutative and switching automata. In this research, the idea of a neutrosophic is incorporated in the general fuzzy finite automata and general fuzzy finite switchboard automata to introduce neutrosophic general finite automata and neutrosophic general finite switchboard automata. Moreover, we define the notion of the neutrosophic subsystem and strong neutrosophic subsystem for both structures. We also establish the relationship between the neutrosophic subsystem and neutrosophic strong subsystem.